1982
DOI: 10.1002/jcp.1041120113
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal responsiveness of a preadipose cell line derived from newborn mouse calvaria

Abstract: We established a clonal preadispose cell line from newborn mouse calvaria. Cells of this cell line, designated MC3T3-G2/PA6, had the capacity to convert to adipose cells, to accumulate triglycerides in their cytoplasm, and to mature to differentiated fat cells in a resting state. This adipose conversion was markedly accelerated by addition of dexamethasone, which was the most potent inducer among the steroid hormones tested. The presence of dexamethasone was needed during the steroid hormones tested. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 19 publications
2
72
0
Order By: Relevance
“…Cell Culture and Synchronization-Experiments were performed with osteoblastic cells, which include rat calvarial osteoblasts, temperature-sensitive SV40 T antigen-transformed human osteoblasts (48), mouse MC3T3 cells (49), osteosarcoma cells (rat ROS17/2.8 and human SAOS-2 cells), chondrocytic cells (mouse ATDC5 clonal teratocarcinoma cells) (50), as well as primary human articular chondrocytes and mesenchymal progenitor cells (mouse C2C12 cells) (51). The osteoblastic cell line MC3T3-E1 was used for the majority of our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture and Synchronization-Experiments were performed with osteoblastic cells, which include rat calvarial osteoblasts, temperature-sensitive SV40 T antigen-transformed human osteoblasts (48), mouse MC3T3 cells (49), osteosarcoma cells (rat ROS17/2.8 and human SAOS-2 cells), chondrocytic cells (mouse ATDC5 clonal teratocarcinoma cells) (50), as well as primary human articular chondrocytes and mesenchymal progenitor cells (mouse C2C12 cells) (51). The osteoblastic cell line MC3T3-E1 was used for the majority of our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…5) Preadipocytes required insulin, glucocorticoids and phosphodiesterase inhibitors, as external inducers, for the trigger of full differentiation into mature adipocytes. [20][21][22] Of those, insulin is well known to play a key role in adipocyte differentiation in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…5) Greenberger reported that corticosteroids accumulated lipids in primary cultured mammalian bone marrow preadipocytes, but insulin did not. 6,7) In addition, the adipogenesis in PA6 cells is also markedly accelerated by the addition of dexamethasone, but insulin is not required for the process.…”
mentioning
confidence: 99%
See 2 more Smart Citations